Suci dan Damai: Peran Ritual Manyanggar dalam Kohesi Sosial - M. Irfan Wahid; Zulkifli; M. Ikhsan Tanggok; Ismatu Ropi; Maida Norahmi (Center for Research and Development of Religious Literature and Heritage, 2026)
This study examines the Manyanggar ritual practiced by the Dayak Bakumpai community in Central Kalimantan as a mechanism for social resilience and conflict resolution. Two research questions guide the inquiry: (1) How does Manyanggar function as a symbolic medium for reinforcing social cohesion? (2) In what ways do community members interpret it as a conflict resolution tool? Drawing on an ethnographic approach, the study integrates in-depth interviews, participatory observation, and document analysis conducted during fieldwork in 2018. Findings demonstrate that Manyanggar operates as a ritual of purification and symbolic communication, facilitating social bonding and the negotiation of cultural and religious identities. Drawing on symbolic interactionism and Alatas's concept of articulatory labor, the study examines how Manyanggar has evolved within an Islamic moral framework while preserving its indigenous social functions. These findings contribute to broader scholarly discussions on indigenous knowledge systems, vernacular Islamization, and the role of ritual performance in contemporary peacebuilding.